FABRIKASI SEL SURYA TERSENSITASI ZAT WARNA ALIZARIN RED S BERBASIS TIO2 - NANOTUBE BERBENTUK SERBUK YANG DIPEROLEH DARI TEKNIK RAPID BREAKDOWN ANODIZATION (RBA) - Linda J Kusumawardani; Jarnuzi Gunlazuardi (Universitas Pakuan, 2016)
TiO2 semiconductor is a material that can be expected to play an important role to solve the energy crisis problem through the utilization of solar energy based on photovoltaic devices. Dye sensitized Solar Cells (DSSC) is a cheaper alternative to silicon-based photovoltaic cells. In this study, TiO2 nanotube powder is using for the DSSC fabrication process which is produced by Rapid Breakdown Anodization (RBA) technique. Alizarin red S is also used as a sensitizer and the counter electrode is prepared from a deposition of 5 mM H2PtCl6 solution as a Pt particle on a fluorine-doped tin oxide (FTO) glass substrate. TiO2 / FTO in DSSC system characterized by FESEM, obtained TiO2 film thickness about 1,6-1,7 ?m and UV-Vis Spectrophotometer. Testing the efficiency value is measured by linear method Sweep Voltametry using potentiostat. The efficiency of converting light energy to electric current obtained is 2.63% and open circuit voltage is 361 mV.Key words : DSSC, Rapid Breakdown Anodization (RBA), Anodization, TiO2 , TiO2 Nanotube-Powder